On the Issue of the Limits of Discretion of the Deputies in Assessing the Annual Report of the Head of the Municipality - SOLOVEV, Sergey Gennadevich (Journal of Advanced Research in Law and Economics, 2018)
The article is devoted to the issue of the limits of discretion of the deputies of the local representative authority in assessing the annual report of the head of the municipality. The author reviews the key issues related to substantive and procedural points of the existing way of assessing the annual report of the head of the municipality by local deputies of the representative authority. Based on the analysis of the theoretical approaches to the discretion of elected representatives of the people, as well as on the study of the practical aspects of the implementation of the procedures for reviewing and evaluating the report of the head of the municipality, directions for improvement of the theoretical construction and legal framework establishing the key aspects of the modern mechanism of evaluation of report of the head of the municipality have been proposed, and a set of legal measures aimed at reducing the possibility of arbitrary decisions of the deputies of the local representative authority in assessing the annual report of the head of the municipality, based solely on their subjective discretion, has been formulated.